Droplet digital PCR for the detection of second-generation tyrosine kinase inhibitor-resistant BCR::ABL1 kinase domain mutations in chronic myeloid leukemia - Soverini, Simona; De Santis, Sara; Martelli, Margherita; Monaldi, Cecilia; Castagnetti, Fausto; Gugliotta, Gabriele; Papayannidis, Cristina; Mancini, Manuela; Bruno, Samantha; Venturi, Claudia; Machova Polakova, Katerina; Ernst, Thomas; et al. (Leukemia, 2022)
One of the indications for BCR::ABL1 mutation testing in chronic myeloid leukemia (CML) is when tyrosine kinase inhibitor therapy (TKI) needs to be changed for unsatisfactory response. In this study, we evaluated a droplet digital PCR (ddPCR)-based multiplex strategy for the detection and quantitation of transcripts harbouring mutations conferring resistance to second-generation TKIs (2GTKIs). Parallel quantitation of e13a2, e14a2 and e1a2 BCR::ABL1 fusion transcripts enables to express results as percentage of mutation positive- over total BCR::ABL1 transcripts. We determined the limit of blank in 60 mutation-negative samples. Accuracy was demonstrated by further analysis of 48 samples already studied by next generation sequencing (NGS). Mutations could be called down to 0.5% and across 3-logs of BCR::ABL1 levels. Retrospective review of BCR::ABL1 NGS results in 513 consecutive CML patients with non-optimal response to first- or second-line TKI therapy suggested that a ddPCR-based approach targeted against 2GTKI-resistant mutations would score samples as mutation-negative in 22% of patients with warning response to imatinib but only in 6% of patients with warning response to 2GTKIs. We conclude ddPCR represents an attractive method for easy, accurate and rapid screening for 2GTKI-resistant mutations impacting on TKI selection, although ddPCR cannot identify compound mutations.
Keywords: Protein Kinase Inhibitors; bcr-abl fúzní proteiny; chemorezistence; polymerázová řetězová reakce; Drug Resistance, Neoplasm; Fusion Proteins, bcr-abl; mutace; Mutation; lidé; Polymerase Chain Reaction; inhibitory proteinkinas; Humans; chronická myeloidní leukemie; Leukemia, Myelogenous, Chronic, BCR-ABL Positive